2019
DOI: 10.1097/md.0000000000013831
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in patients affected by breast ductal carcinoma in situ with and without microinvasion

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…The incidence of lymph node metastasis in microinvasive breast cancer was 5.5%-12%. 10 , 18 , 19 The proportion of lymph node metastasis was 6.6% (8/121) in the present study, which was similar to that reported in the literature. At the same time, the size of CIS reported in the literature is similar to the tumor size range in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of lymph node metastasis in microinvasive breast cancer was 5.5%-12%. 10 , 18 , 19 The proportion of lymph node metastasis was 6.6% (8/121) in the present study, which was similar to that reported in the literature. At the same time, the size of CIS reported in the literature is similar to the tumor size range in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Table 1 shows a description of the included samples. The median age at breast cancer surgery was 55 years (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), and the median BMI was 25 kg/m2 (IQR [22][23][24][25][26][27][28][29]. In 99.26 and 8.82% of cases, respectively, adjuvant and neoadjuvant chemotherapy was administered.…”
Section: Population Descriptionmentioning
confidence: 99%
“…Changes in the analysis of LN using serial sections coupled with cytokeratin immunodetection by IHC has increased ITC and micrometastases identification. Depending on the studies, SLN removal associated with exhaustive LN analysis has increased the incidence of LN involvement varying from 0.9% to 8% (49)(50)(51)(52)(53). In these studies, most of ALN involvements were limited to isolated or small clusters of epithelial cells (49).…”
Section: Slnb Indications and Contraindications In Case Of Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%